POTENSI WISATA BANGUNAN KOLONIAL DI KOTA MALANG - Debora Budiyono; Riyanto Djoko (BUANA SAINS, 2010)
The research about potential of colonial building tourism in Malang city aimed to identify buildings related to the colonial history in Malang city, analyze the historical value and point of interesting view of potential of colonial building tourism which could be developed in Malang city. This research was done on the several areas in Malang city i.e. a) East-West stripe covered: Alun-Alun Tugu area, Kahuripan street, Semeru street and Ijen street and b) North-South stripe covered: Jaksa Agung Suprapto street, Basuki Rahmad street, Alu-Alun Merdeka area and Chinatown residence. The method used was descriptive method. Furthermore, data analysis method used two step i.e. 1) building value considered from sicio-culture aspect and 2) determination of potential of colonial building tourism. Based on socio-culture aspect analyzed, there were 12 locations having different potential of colonial building tourism. The locations having the highest value of socio-culture i.e. Ijen area, whereas the lowest was Kahuripan street